One face of a transmembrane helix is crucial in mechanosensitive channel gating - Ou, Xiaorong (The National Academy of Sciences, 1998)
MscL is a mechanosensitive channel in bacteria that responds directly to membrane tension by opening a large conductance pore. To determine functionally important residues within this molecule, we have randomly mutagenized mscL, expressed the genes in living bacteria, and screened for gain-of-function mutants with hampered growth. Expression of these genes caused leakage of cytoplasmic solutes on little or no hypo-osmotic stress. In excised patches, the mutant channels gated at membrane tensions that are less than that required for the gating of the wild-type MscL. Hence, the data suggest that the slowed or no-growth phenotype is caused by solute loss because of inappropriate gating of the channel. Most of the mutations mapped to the first transmembrane domain. When this domain is modeled as an α-helix, the most severe mutations are substitutions of smaller amino acids (three glycines and one valine) on one facet, suggesting an important role for this structure in MS channel gating.